Comparison Between Pars Plana Vitrectomy with and without Encircling Band in the Treatment of Pediatric Traumatic Rhegmatogenous Retinal Detachment - Ghoraba HH; Mansour HO; Abdelhafez MA; El Gouhary SM; Zaky AG; Heikal MA; Ghali AAA (Clinical Ophthalmology, 2020)
Hammouda Hamdy Ghoraba,1,2 Hosam Othman Mansour,1,3 Mohamed Ahmed Abdelhafez,1 Sameh Mohamed El Gouhary,4 Adel Galal Zaky,4 Mohamed Amin Heikal,5 Ali Ahmed Ali Ghali3 1Magrabi Eye Hospital, Tanta, Egypt; 2Tanta University, Tanta, Egypt; 3Al Azhar University, Damietta Branch, New Damietta, Egypt; 4Meunofia University, Meunofia, Egypt; 5Benha University, Benha, EgyptCorrespondence: Hosam Othman MansourAl Azhar University, Damietta Branch, New Damietta, EgyptTel +201001559282Email drhmansor@yahoo.comBackground and Objectives: To compare anatomical and visual results of pars plana vitrectomy (PPV) with or without additional encircling band in the management of pediatric traumatic rhegmatogenous retinal detachment (RD) in a tertiary referral center.Methods: A retrospective review of children diagnosed with traumatic rhegmatogenous retinal detachment treated by pars plana vitrectomy with or without encircling band.Results: One hundred thirty-nine eyes of 139 children diagnosed with traumatic rhegmatogenous retinal detachment. Surgeries were performed between May 2011 and November 2016. Patients were followed up for at least 18 months after last intervention. The included eyes were categorized into two groups. Group A (vitrectomy with additional encircling band) included 72 eyes of 72 children; 58 boys and 14 girls. Group B (vitrectomy without encircling band) included 67 eyes of 67 children; 58 boys and 9 girls. In group A, the mean age was 9.21± 3.24. Attached retina was achieved in 61% (44 out of 72 eyes), of which 34 eyes remained attached after silicon oil removal, and 10 eyes remained attached under silicon oil tamponade. Recurrent RD under oil was present in 28 eyes (38.9%). In group B, the mean age was 11.06± 3.64. Attached retina was present in 61.2% (41 out of 67 eyes), of which 30 eyes remained attached after oil removal, and 11 eyes remained attached under silicon oil tamponade. Recurrent RD was present in 26 eyes (38.8%). In group A, the final visual acuity (VA) ranged from NLP to 0.5; 58.7% of patients achieved VA more than counting fingers at 1 meter, and 34.6% of patients achieved VA of 0.05 or more. In group B, the final postoperative VA ranged from NLP to 0.9; 16% of patients achieved VA from counting fingers at 1 meter to 0.05, and 29.2% achieved VA of 0.05 or more.Conclusion: Although no statistically significant difference between the two groups (combined vitrectomy and encircling band versus vitrectomy alone in pediatric traumatic retinal detachment), it is wise to consider adding encircling band in severe trauma cases.Keywords: trauma, pediatric retinal detachment, encircling band, pars plana vitrectomy, silicon oil